Changes in antigen-specific T cell number and function during oral desensitization in cow’s milk allergy enabled with omalizumab - Bedoret, D (2012)
Food allergy is a major public health problem for which there is no effective treatment. We examined the immunological changes that occurred in a group of children with significant cow’s milk allergy undergoing a novel and rapid high dose oral desensitization protocol enabled by treatment with omalizumab (anti-IgE mAb). Within a week of treatment, the CD4(+) T cell response to milk was nearly eliminated, suggesting anergy in, or deletion of, milk-specific CD4(+) T cells. Over the following three months while the subjects remained on high doses of daily oral milk, the CD4(+) T cell response returned, characterized by a shift from IL-4 to IFN-γ production. Desensitization was also associated with reduction in milk-specific IgE and a 15-fold increase in milk-specific IgG4. These studies suggest that high dose oral allergen desensitization may be associated with deletion of allergen-specific T cells, without the apparent development of allergen-specific Foxp3(+) regulatory T cells.